Wing shape differences between flying and non-flying individuals of six Triatoma species (Hemiptera: Reduviidae: Triatominae) - Fernanda Cristina de Oliveira Firmino; Cleber Galvão; Dayse Rocha (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: Despite numerous reports of triatomines invading homes through flight, experimental studies investigating this ability under laboratory conditions remain scarce. Flight ability varies between individuals (males and females) of the same species, and wing shape modifications may be associated with the flight capacity of these vectors. Therefore, studies on this topic are crucial for the early identification of species with a greater propensity to invade human dwellings and for the implementation of appropriate surveillance and vector control strategies. However, even when exposed to the same nutritional and environmental conditions, triatomines demonstrate a range of flight abilities. To date, it remains unclear whether differences in wing morphology play a decisive role in determining this behavior. As an initial approach to addressing this issue, the present study aimed to determine whether morphometric differences exist in the wings of flying and non-flying individuals from six species of the genus Triatoma: Triatoma costalimai, Triatoma klugi, Triatoma matogrossensis, Triatoma rubrovaria, Triatoma vandae, and Triatoma williami. Methods: This study employed geometric morphometrics to investigate differences in wing size and shape between flying and non-flying individuals from six Triatoma species. Results: The findings indicated a variation in wing size between sexes. Additionally, shape variations were observed between flying and non-flying insects, particularly in females. Conclusions: Geometric morphometrics effectively identified distinct wing shape patterns in flying and non-flying specimens from six Triatoma species, revealing differences that may aid in identifying species with greater active dispersal capacity.